ANALISIS EFISIENSI TEORETIS KONDISI FABRIC FILTER DI UNIT COAL MILL PADA PT SG DI TUBAN JAWA TIMUR - Huboyo, Haryono Setiyo (Universitas Diponegoro, 2007)
Cement Industrial activities produces various pollutants mainly dust pollutant and gases pollutants. These pollutants come up from material handling, production process (treatment, combustion and finish mill) and packing process. PT SG has done any steps to controll its pollutant i.e ambient and emission pollutant measurements and conducting abatement. Bag filters in coal mill unit shows an excellent performance since its real dust output concentration only 22.9 and 13.4 mg/m3 far below emission standard 80 mg/m3. Theoretical efficiency of this device was assessed using design criteria, limited assumption and secondary relevant literature. Based on secondary data the efficiency was 99.9% (higher than EPA standard 99.5%). Its values are somewhat different using real output concentration showing 99.29% and 99.58%. These differences were subjected to limited design specification data and fluid properties exist.